Loop Recorder Detected High Rate of Atrial Fibrillation Recurrence after a Single Balloon- or Basket-Based Ablation of Paroxysmal Atrial Fibrillation: Results of the MACPAF Study - Schirdewan, Alexander; Herm, Juliane; Roser, Mattias; Landmesser, Ulf; Endres, Matthias; Koch, Lydia; Haeusler, Karl Georg (Frontiers in Cardiovascular Medicine, 2017)
Purpose Pulmonary vein isolation (PVI) is an established approach to treat symptomatic non-permanent atrial fibrillation (AF). Detecting AF recurrence after PVI is important, if discontinuation of oral anticoagulation after ablation is considered. Methods Patients with symptomatic paroxysmal AF were enrolled in the prospective randomized MACPAF study, comparing efficacy and safety of the HD Mesh ablator® (C.R. Bard, Lowell, USA) and the Arctic Front® (Medtronic, Minneapolis, USA) catheter. Rhythm status post PVI was closely monitored for one year using the implantable loop recorder (ILR) Reveal XT® (Medtronic Minneapolis, USA). Results The study was terminated after the first interim analysis due to the inability of the HD Mesh Ablator® to achieve the predefined primary study endpoint, an exit- block of all PVs. After a 90-day blanking period, 23 (62.2%) out of 37 study patients (median 63.0 years; 41% female) had at least one episode of AF. AF recurrence was associated with AF episodes during the blanking period (HR 5.10 [95%CI 1.21–21.4]; p=0.038), and a common left-sided PV ostium (HR 4.17 [95%CI 1.48-11.8]; p=0.039) but not with catheter type, age, gender, cardiovascular risk profile or left atrial volume. There was a trend towards AF recurrence in patients without complete PVI of all PV (p=0.095). Overall, 337 (59.4%) out of 566 ILR-detected episodes represented AF. Comparing patients with AF recurrence to those without, there was no difference in cognitive performance six months post ablation. Conclusion Using an ILR, in more than 60% of all patients with paroxysmal AF a recurrence of AF was detected within 12 months after ablation. In patients with a common PV ostium, the first generation balloon-based catheter are obviously less effective.